2013
DOI: 10.1167/iovs.12-10536
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Retinal Vasculature in Cystathionine-Beta-Synthase Mutant Mice, a Model of Hyperhomocysteinemia

Abstract: PURPOSE. Mice with moderate/severe hyperhomocysteinemia due to deficiency or absence of the cbs gene encoding cystathionine-beta-synthase (CBS) have marked retinal disruption, ganglion cell loss, optic nerve mitochondrial dysfunction, and ERG defects; those with mild hyperhomocysteinemia have delayed retinal morphological/functional phenotype. Excess homocysteine is a risk factor for cardiovascular diseases; however, it is not known whether excess homocysteine alters retinal vasculature. METHODS. Cbs, and cbs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 35 publications
(55 reference statements)
3
44
0
2
Order By: Relevance
“…In this study, we used the FAL model by employing a genetically engineered mouse model (CBS +/À ) mimicking HHcy conditions as seen in HHcy patients for the purpose of studying the postischemic neoangiogenesis phenomenon during HHcy. Our results add to the growing body of evidence that HHcy is associated with defective neoangiogenesis as shown in other in vivo experiments (Tan et al 2006;Tawfik et al 2013). Earlier, studies also showed that high Hcy (HHcy) has a profound inhibitory effect on EC proliferation and their migration (Cai et al 2007;Li et al 2006;Ozsvari et al 2010;Papapetropoulos et al 2009;Tan et al 2006).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, we used the FAL model by employing a genetically engineered mouse model (CBS +/À ) mimicking HHcy conditions as seen in HHcy patients for the purpose of studying the postischemic neoangiogenesis phenomenon during HHcy. Our results add to the growing body of evidence that HHcy is associated with defective neoangiogenesis as shown in other in vivo experiments (Tan et al 2006;Tawfik et al 2013). Earlier, studies also showed that high Hcy (HHcy) has a profound inhibitory effect on EC proliferation and their migration (Cai et al 2007;Li et al 2006;Ozsvari et al 2010;Papapetropoulos et al 2009;Tan et al 2006).…”
Section: Discussionsupporting
confidence: 79%
“…; Tawfik et al. ). Earlier, studies also showed that high Hcy (HHcy) has a profound inhibitory effect on EC proliferation and their migration (Cai et al.…”
Section: Discussionmentioning
confidence: 98%
“…Three-week-old Cbs −/− mice have a seven-fold elevation of tHcy in the retina and have distinct alterations in retinal architecture and abnormal electroretinograms [59, 60]. Follow-up studies indicated that there was vascular leakage in the retina as determined by angiography [61]. More recently, it has been shown that Cbs −/− mice have altered retinal pigment epithelial structure [62].…”
Section: Eye Phenotypesmentioning
confidence: 99%
“…VEGF, a potent mediator of vascular permeability in the retina is also implicated in retinal neovascularization in ischemic retinopathies (76)(77)(78)(79)(80)(81). The aqueous levels ofVEGF and IL-6 are correlated significantly with the severity of macular edema.…”
mentioning
confidence: 99%